Epidemiology and Management of Immune Thrombocytopenia in Adult Patients in Algeria: A Non-interventional, Longitudinal, Nationwide Estimation Study - Bekadja, Mohamed Amine; Bradai, Mohamed; Hamdi, Selma; Boudjerra, Nadia; Saidi, Mahdia; Grifi, Fatiha; Saidi, Djamel; Mesli, Naima; Zouaoui, Zahia; Lakhdari, Nourredine; Mehalhal, Nemra; Sidi Mansourl, Noureddine; et al. (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Globally, immune thrombocytopenia (ITP) affects more women than men with a higher incidence in older patients. However, data on the epidemiology and treatment regimen for ITP is limited and varies across different countries. In this non-interventional, longitudinal, nationwide estimation study, we present incidence (by age, sex, and diagnosis stage), prevalence, characteristics, and treatment regimens of ITP in Algeria. Methods: Patients ≥16 years of age with prevalent (diagnosed before September 3, 2017) or incident (diagnosed between September 3, 2017–August 30, 2018) ITP were involved in this study. Patient data were collected from public hospitals and the incidence and prevalence estimates were made using Poisson distributions (95% confidence interval [CI]). Results: Of 1,746 patients from 16 hematology departments, 1,159 were included in the study; 173 (14.9%) were incident and 986 (85.1%) were prevalent patients with ITP. The median (quartiles) age of patients at diagnosis was 36 (25, 50) years; 895 (77.2%) were women. At inclusion, 88.2% of patients were asymptomatic and 3.8% had severe bleeding. The national incidence was 0.85 (0.75–0.96) and prevalence was 5.65 (5.39–5.93) per 100,000 population. The incidence of ITP in women (1.18 [1.02–1.37]/100,000 population) was higher versus men (0.54 [0.43–0.67]/ 100,000 population). The incidence of ITP was four times higher in the ≥75 years cohort (2.37 [1.60–3.51]/100,000 population) versus that observed in the 15–35-years age cohort (0.54 [0.43–0.68]/100,000 population). First-line treatments included corticosteroids (80.8%), intravenous immunoglobulin (3.4%), and rituximab (1.3%); 17.4% of patients underwent splenectomy as a third-line procedure. Conclusion: The overall incidence rate of ITP in Algeria was low. However, the incidence trends are similar to those reported globally, with high incidence reported in women and older patients. Corticosteroids were the most prescribed therapy, and few patients were prescribed thrombopoietin receptor agonists before opting for splenectomy.